(untitled) (Acta Scientiarum. Health Sciences, 2020)
The objective of this study was to analyze the sociodemographic, clinical and therapeutic profile of psychiatric hospitalizations related to mental and behavioral disorders. This is an analytical cross-sectional study conducted in a hospital reference in psychiatric treatment in Teresina, Piauí, Brazil. The data were collected with the aid of a form to characterize the sociodemographic, clinical and therapeutic aspects of hospitalizations. The SPSS version 22.0 was used. There was analysis of 291 medical records of patients admitted during the period from February to May 2018, which revealed the year 2018 with the highest rate of psychiatric hospitalization, 239 (82.1%). There was prevalence of men 184 (63.2%), unmarried 209 (71.8%), with a mean age of 38.4 years. There was also a predominance of patients with low schooling. The sex was statistically associated with the use of illicit drugs (p:0.003), suicide attempts (p:0.04) and type of admission (p:0.006). On the other hand, schooling was associated with abandonment (p:0.008); suicide attempt (p:0.033) and previous hospitalizations (p:0.006). Many factors and comorbidities increase the possibility of the patient re- hospitalization.